The development of the teaching concept of musical stage art - Lian, Xiang (Linguistics and Culture Review, 2021)
In the work showed that the basis of teaching the history of choreographic art is the willingness of teachers and listeners to perceive choreography as an art. For this, the authors of the article have developed a concept that characterizes the approbation of teaching the history of choreographic art at the level of its perception by university students. The authors distinguish the features of teaching the history of choreographic art not only as a historical course with the formation of only the knowledge component. The possibilities of preparing listeners for practical activities are determining. The authors first of all, determining the psychological readiness, which is expressed as the level of mastering information. The authors marked that this approach allows us to form a directional approach to increasing interest in art, as well as to filling an understanding of the value not only of choreography as an art form, but also as a pedagogical strategy and practice. The novelty of the research is the formation of the concept of art history as a teaching strategy in the overall structure of the process of pedagogy and psychology.